Sonographic Assessment of the Vaginal Vault Following Hysterectomy - Haines, C. J. (Institutional Knowledge at Singapore Management University, 1995)
A procedure for the robust estimation of a time series regression model is developed. This procedure is based on the generalised least squares transformation (GLST) technique. $M$-estimates of the hyperparameters of the model are produced by a robust filt